Metodologia analítica para determinação de HPAs leves em águas e solos por extração em fase sólida com membrana de náilon, espectrofluorimetria e calibração de segunda ordem - Siqueira, Alcides da Silva (2019)
Aromatic Polycyclic Hydrocarbons are compounds formed by two or more condensed aromatic rings and constituting a group of more than one hundred substances. Sixteen of these are monitored because of increased human exposure, toxicity, and possible carcinogenic and / or mutagenic effects. They are emerging pollutants formed by incomplete combustion that are generated in large quantity and continuously by human activity. The analytical methods used to determine these analytes are time consuming, high solvent consumption and require extraction and / or preconcentration. Soxhlet extraction is recommended and the concentration step of the organic extract is generally done by roto-evaporation or nitrogen flow. In these procedures, evaporative losses occur of more volatile species, such anthracene and phenanthrene. In this context, the solid phase extraction with membrane allied to the fluorescence spectroscopy directly on the membrane shows a sensitive, fast and low cost alternative that, together with the higher order calibration, allows to q uantify these compounds in several matrices. This set of techniques has a limitation for its application in real systems: possible suspended particles in the sample solution are retained in the membrane after the extraction and can compromise the detection of fluorescence by filter effect, making it impossible to apply to matrices that are more complex. Thus, in the present work a methodology was developed for the determination of ANT and FEN in water and soil samples using solid phase extraction in nylon membrane, direct total membrane fluorescence spectroscopy and second order calibration. The strategy used to avoid the interference of particulates retained in the filtration was to perform the detection on the opposite side of the filter. The results showed that the proposed method allows to identify phenanthrene and anthracene, and to quantify phenanthrene in a simple, fast and efficient way in samples of soils and tap water containing the two isomers.